Low-cost and home-made immersive systems - Kuntz, Sébastien; Cíger, Ján (International Journal of Virtual Reality, 2012)
A lot of professionals or hobbyists at home would like to create their own immersive virtual reality systems for cheap and taking little space. We offer two examples of such "home-made" systems using the cheapest hardware possible while maintaining a good level of immersion: the first system is based on a projector (VRKit-Wall) and cost around 1000, while the second system is based on a head-mounted display (VRKit-HMD) and costs between 600 and 1000. We also propose a standardization of those systems in order to enable simple application sharing. Finally, we describe a method to calibrate the stereoscopy of a NVIDIA 3D Vision system.